Academic performance, family support, interest and career decision among undergraduate students in Nigeria - Salisu Yunusa; Ibrahim Sani Mainagge; Sani Haruna; Abdulwahab Ibrahim (UIN Raden Mas Said Surakarta, 2022)
Studies in the five recent years have shown that more than half of Nigerian undergraduate students changed their study programs and career decisions. Notwithstanding this fact, lack of research addresses factors that affect the Nigerian undergraduate students made such a decision. Therefore, the present study aims to explore the influence of academic performance, family support, and interest on career decision of undergraduate students in Jigawa state Nigeria. A set of questionnaires was utilized as an instrument to collect the data from a total of 373 Nigerian undergraduate students. Drawing on correlational study using structural equation modelling approach, this study revealed that academic reason (t=3.452; β=0.191; P=0.001) and family support (t=4.554; β=0.234; P=0.000) have statistically significant correlation with career decision making of the students. On the contrary, interest was empirically proven to not have a significant relationship with the career decision making (t=0.899; β=-.056; P=0.369). Thus, it is concluded that academic reason and family support play more crucial role in determining the career decision of undergraduate students in Nigeria than their interest abilities. This study provides implication for Nigerian government and non-government organizations to massively educate parents and families so that they can encourage their children’s career paths and support their career choices.